Enhancing inhibitory control and risky decision- making with brain stimulation: A randomized and sham-controlled study - Farshad, Sabah; Abharianb, Peyman H.; Malaei, Fereidoun; Safari, Mir-Shahram (International Journal of Psychosocial Rehabilitation, 2020)
Inhibitory control and risky decision making are critical cognitive functions, particularly to determine more appropriate behaviors that are compatible with achieving goals and preventing unwanted outcomes. Multiple studies have measured the efficacy of brain stimulation to enhance individuals’ cognitive abilities. Although some of the results show positive achievements, the generalizability of the results remains open to doubt, particularly in young population contries. Current research examines the effects of cognitive training and brain stimulation to enhancing inhibitory control and risky decision-making in healthy adults in Tehran utilizing computer games training associated with brain stimulation. The experiment involved four groups of 60 healthy volunteers who were residents of Tehran and randomly assigned to groups. A pre-test with post-test analysis, including Go/NoGo and BART tasks used to compare the groups. A single session intervention was applied using 30 minutes of 2 mA tDCS, as well as a computerized game as cognitive training. The control group went under sham-tDCS with a non-cognitive game. Contrary to the various prior studies, the results of the statistical analyses of the data from experimental and control groups showed no meaningful difference. Based on the results of this study, there is no significant effect of rIFG tDCS on the scores of inhibitory control and risky decision-making tasks. This study collected, summarized, and discussed a considerable amount of wide-ranging of relevant investigations. Despite limitations in the number of subjects and stimulation sessions that restricts us to make an exact conclusion, if the same results will appear with the same brain’s region, the efficacy of tDCS on enhancing examined functions through rIFG is faced with doubt. It seems that the protocols used in this study require to be repeated in similar studies with more subjects. Furthermore, instead of a single session of intervention, multiple sessions of intervention are suggested.